Living Hadis dalam Pembentukan Islam: Teori, Praktik, dan Tantangan - Rafli, Rahmat; Ahmad, La Ode Ismail; Usman Ali, Asiqoh (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Living Hadith refers to the actualization of the Prophet Muhammad’s sayings and teachings within the social, cultural, educational, and da’wah life of Muslim communities. This approach emphasizes that hadith is not merely a textual tradition but a living guide manifested in daily religious and social practices. Through rituals such as the Prophet’s Birthday (Maulid), communal prayers (tahlilan), almsgiving, and grave visits, hadith becomes a moral and spiritual source shaping Muslim character and social solidarity. In education and da’wah, hadith values are internalized through learning, role modeling, and digital media. However, the development of Living Hadith faces academic challenges due to the lack of standardized methodology, as well as socio-cultural issues like syncretism and misinterpretation. Modernity and globalization also demand new interpretations to ensure the relevance of hadith in the digital era. This study concludes that Living Hadith serves as a bridge between divine revelation and social reality, portraying Islam as a dynamic, contextual, and universal religion of mercy (rahmatan lil ‘alamin).